Alkaline phosphatase for immunocytochemical labelling: problems with endogenous enzyme activity. Issue 12 (December 1981) - Bulman, A S; Heyderman, E
Abstract : Alkaline phosphatase may be used as a label for immunocytochemistry and can be demonstrated in tissue sections using the single step naphthol phosphate method. Endogenous enzyme activity may not be destroyed by fixation in formalin, formol alcohol, Carnoy's or Baker's solutions and should be inhibited before results are assessed. Either Bouin's solution or periodic acid followed by potassium borohydride are satisfactory inhibitor and do not adversely affect immunocytochemical results.